IMPROVING TEACHING TECHNOLOGIES FOR C1-LEVEL PROSPECTIVE LANGUAGE TEACHERS: A SOCIO-PSYCHOLOGICAL APPROACH (International journal of artificial intelligence, 2026)
This article explores the theoretical foundations for improving teaching technologies based on socio-psychological characteristics of prospective foreign language teachers at the C1 level. The study emphasizes the importance of integrating learners’ psychological traits, social interaction skills, motivation, and cognitive abilities into the process of developing effective teaching strategies. It analyzes modern pedagogical approaches and highlights the role of communicative competence, emotional intelligence, and intercultural awareness in shaping professional language teachers. The research also examines the challenges faced in aligning teaching technologies with individual differences and proposes methods for enhancing instructional effectiveness. The findings suggest that incorporating socio-psychological factors into teaching methodologies significantly contributes to the development of highly qualified foreign language teachers with advanced language proficiency.